Creative Black and White, 2nd Edition - Davis, Harold (Rocky Nook, 2019)
Black-and-white photography poses unique challenges; without color to guide the eye, contrast, lighting, and composition take on even more importance. In Creative Black and White, 2nd Edition, renowned photographer Harold Davis explains these elements and demonstrates the basic rules of black and white photography, as well as when and how to break them. He breaks through the complexity of this photographic medium, explores opportunities for black-and-white imagery, and shows how to capitalize on each and every one of them. This new, revised, and expanded edition brings the tools up to date with extended sections on monochrome in Lightroom, Photoshop, and related plugins. TABLE OF CONTENTS THE MONOCHROMATIC VISION Past, Present, and Future Thinking in Black and White Contrast Color Implied The Tonal Landscape Visual Implication Seeing in Black and White Pre-Visualization Techniques Black and White Composition Framing Patterns and Lines Shape and Form High Key Low Key Shades of Gray Finding Monochromatic Subjects Black and White at Night Photographing People Portraiture in Black and White BLACK AND WHITE IN THE DIGITAL ERA Digital Black and White Roadmap The RAW Advantage Black and White in Adobe Camera RAW Black and White in Lightroom Grayscale Conversion Using Presets HSL Conversion Exposure Gradients and Adjustments Exporting Virtual Copies into Photoshop as Layers Multiple Layers and Masking in Photoshop Multi-RAW Processing in Photoshop Black and White in Photoshop Blending with Black Using the Channel Mixer Black & White Adjustment Layers Silver Efex Pro Topaz B&W Effects OnOne Perfect B&W The Digital Analog to the Analog Zone System Combining Conversions in Photoshop CREATIVE BLACK AND WHITE OPPORTUNITIES Lighting and Monochromatic Photos Creating High-Key Effects Creating Low-Key Effects HDR in Black and White Shooting for HDR Using HDR Software Toning and Tinting Tinting with a Black & White Adjustment Layer Split Toning The Ansel Adams Effect Selective Color Hand Coloring Using LAB Color Inverting the L Channel Equalizing LAB Channels Swapping Tonalities Using Blending Modes LAB Inversions Soft Focus Adding Soft Focus Pinhole Effect Solarization Using Curves to Solarize an Image Simulating the Blossfeldt Effect Duotone and Tritone Effects Adding and Reducing Noise Film Effects Infrared Camera Conversions Infrared Conversion without an IR Camera Creating X-Ray Images MOBILE BLACK AND WHITE Black and White using a Cell Phone Camera Worki...